2001
DOI: 10.1002/1521-401x(200109)29:2/3<100::aid-aheh100>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyphomycetes Species on Floating Plant Spores and Pollen

Abstract: The authors investigated the hyphomycete species growing on the spores and pollen of 27 plant taxa in the water of three water body varying in trophic state. A total of 82 hyphomycete species were noted. The most common species were Acrodictys bambusicola, Angulospora aquatica, Heliscus submersus, Lemonniera aquatica, Microstella pluvioriens, Trinacrium subtile, and Varicosporum delicatum. The fewest species were found to colonize pollen grains of Typha angustifolia (11 species), the most were observed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Stream fungi are vitally important for energy transformation of submerged leaf litter ( Baldy et al , 1995 ; Gessner & Chauvet, 1994 ; Gulis & Suberkropp, 2003 ; Hieber & Gessner, 2002 ). FPOM may also be blown in or washed in from adjacent forest soils, or originate from sloughed-off algal biofilms, consist of plant spores and pollen ( Czeczuga & Orlowska, 2001 ), or be produced by flocculation of DOM, with or without microbial participation ( Lush & Hynes, 1973 ; Wotton, 1990 ). Due to the many biological processes involving CPOM and FPOM, bacteria and fungal spores will also contribute to the pool of stream FPOM ( Bärlocher & Brendelberger, 2004 ; Callisto & Graça, 2013 ; Edwards & Meyer, 1987 ; Gleason et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stream fungi are vitally important for energy transformation of submerged leaf litter ( Baldy et al , 1995 ; Gessner & Chauvet, 1994 ; Gulis & Suberkropp, 2003 ; Hieber & Gessner, 2002 ). FPOM may also be blown in or washed in from adjacent forest soils, or originate from sloughed-off algal biofilms, consist of plant spores and pollen ( Czeczuga & Orlowska, 2001 ), or be produced by flocculation of DOM, with or without microbial participation ( Lush & Hynes, 1973 ; Wotton, 1990 ). Due to the many biological processes involving CPOM and FPOM, bacteria and fungal spores will also contribute to the pool of stream FPOM ( Bärlocher & Brendelberger, 2004 ; Callisto & Graça, 2013 ; Edwards & Meyer, 1987 ; Gleason et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well defined that carotenoid content in the diet and diet formulation significantly affects the carotenoid content in animal tissues. This phenomenon is also characteristic for fish (CZECZUGA and CZERPAK 1976;NEAMTU et al 1976;KAMATA et al 1977;LEE et al 1978). BAUERNFEIND (1972) has indicated that some of plant origin carotenoids are converted in animal body to vitamin A.…”
Section: Introductionmentioning
confidence: 77%
“…It has been indicated in the previous study (CZECZUGA 1979b) that with increasing age of common carp, the amount and variety of carotenoids is increasing too. However, in carp as well as in other fish species, the kind of the diet is decisive factor in the presence of carotenoid pool in the body (CZECZUGA and CZERPAK 1976;CZECZUGA 1975CZECZUGA , 1979a). This can be an explanation to the appearance in carp body carotenoids of apo-carotenals group.…”
Section: Discussionmentioning
confidence: 99%